Changes in Coconut Water Quality (Cocos nucifera L) During the Storage Process - Andini, Nurlisa; Muhidong, Junaedi; Haerani; Intan Permata Hati, Febriana (Program Studi Teknik Pertanian Universitas Hasanuddin, 2024)
Coconut water (Cocos nucifera L.) is a natural beverage widely recognized for its high nutritional and health benefits. It contains essential electrolytes such as potassium, magnesium, and calcium, along with various vitamins and antioxidants; however, the quality deteriorates over time during storage. This study compares changes in the quality of young and mature coconut water stored at cold and ambient temperatures over a specific period of time. The research method includes measuring turbidity levels, pH, and total dissolved solids (TDS). The results indicate that both young and mature coconut water experience degradation in quality during storage, although at different rates. Storage at ambient temperature leads to a more rapid decline in quality than cold storage for both maturity types. Additionally, microbial growth is more frequently detected in coconut water stored at ambient temperature, particularly in mature coconut water. This study summarises that the quality of young and mature coconut water is influenced by storage temperature, with mature coconut water deteriorating at a higher rate. These findings can be recommended for storing coconut water at cold temperatures and consuming it shortly after opening it.